2017
DOI: 10.1038/mp.2016.239
|View full text |Cite
|
Sign up to set email alerts
|

An endophenotype approach to the genetics of alcohol dependence: a genome wide association study of fast beta EEG in families of African ancestry

Abstract: Fast beta (20–28 Hz) electroencephalogram (EEG) oscillatory activity may be a useful endophenotype for studying the genetics of disorders characterized by neural hyperexcitability, including substance use disorders (SUDs). However, the genetic underpinnings of fast beta EEG have not previously been studied in a population of African-American ancestry (AA). In a sample of 2382 AA individuals from 482 families drawn from the Collaborative Study on the Genetics of Alcoholism (COGA), we performed a genome-wide ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 90 publications
(112 reference statements)
0
35
0
Order By: Relevance
“…This bodes well for future GWAS of additional EEG parameters. For example, two recently published GWASs of bipolar EEG from families of African and European ancestry reported genome-wide signal at 3q26 and 6q22, respectively [Meyers et al, 2017a; Meyers et al, 2017b]. Bipolar EEG derivations show more localized activity than other EEG derivations and remove volume conduction effects, and have been particularly successful as a biomarker of alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bodes well for future GWAS of additional EEG parameters. For example, two recently published GWASs of bipolar EEG from families of African and European ancestry reported genome-wide signal at 3q26 and 6q22, respectively [Meyers et al, 2017a; Meyers et al, 2017b]. Bipolar EEG derivations show more localized activity than other EEG derivations and remove volume conduction effects, and have been particularly successful as a biomarker of alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The first genome-wide association study of EEG oscillation strength showed an association between SGIP1 and theta oscillations in both Native American and European Ancestry samples. Two recent studies from the Collaborative Study on the Genetics of Alcoholism (COGA) associated several intergenic SNPs at 6q22 in a European sample [Meyers et al, 2017a], and at 3q26 in African American ancestry [Meyers et al, 2017b] for >20 Hz fast beta oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple genome-wide arrays were used to genotype the COGA sample 23,[39][40][41] Text) using SHAPEIT2 42 and Minimac3. 43 Imputed SNPs with R 2 < 0.30 were excluded, and genotype probabilities were converted to best-guess genotypes if ≥0.90.…”
Section: Genotyping Quality Review Ancestry and Imputationmentioning
confidence: 99%
“…Given the current state of the psychiatric/endophenotype behavioral genetics field, it is difficult to speculate on the specific genetic mechanisms that give rise to the AUD-theta genetic correlation. The search to identify specific genetic variants of several task-based EEG-based endophenotypes, including midfrontal theta power, has so far proven largely unsuccessful (Iacono et al., 2017; Malone, McGue, & Iacono, 2017; although see Smit et al, 2018, and Meyers et al, 2017, for genomewide association studies [GWAS] of resting state EEG oscillatory power). Evidence suggests that psychophysiological endophenotypes, like psychiatric phenotypes, are highly polygenic and genetically complex, with individual common variants explaining a very small fraction of the phenotypic variance.…”
Section: Discussionmentioning
confidence: 99%